389. BENEFITS OF BILATERAL THORACOSCOPIC SURGERY IN THE PRONE POSITION FOR A LARGE ESOPHAGEAL TUMOR. (24th September 2022) - Uemura, Norihisa; Ishihara, Makoto; Saeki, Satomi; Ito, Takaaki; Tsukahara, Tetsuo; Tabata, Koki; Yamashita, Hiromasa; Takeuchi, Mamiko; Arai, Toshiyuki; Amemiya, Takeshi
Abstract: Esophageal gastrointestinal stromal tumors (GISTs) are relatively less symptomatic and may have a significantly large tumor diameter at diagnosis. Large esophageal tumors are difficult to resect because it is tough to maintain the surgical field in the narrow mediastinal region. In addition, because GIST has a risk of dissemination if the tumor collapses during surgery, it must be resected with as little force as possible. We herein report a middle and lower thoracic esophageal GIST with a maximum lateral diameter of 12 cm that could be safely resected by a bilateral thoracoscopic approach in the prone position. The case was that of a 70-year-old man. Since his tumor diameter was large and the surrounding organs were severely compressed, it was deemed to be borderline resectable, and preoperative chemotherapy with imatinib was decided. However, administration of imatinib did not result in tumor shrinkage, and interstitial pneumonia occurred. Thus, the final decision was to resect it. It was difficult to remove the left side of the tumor by normal thoracoscopic operation from the right side as the tumor was large. There was also the risk of the tumor collapsing due to unreasonable traction. Therefore, we selected a surgical procedure in which the left and right sides of the tumor were detached by bilateral thoracoscopic operation in the prone position and then the tumor was removed from the abdominal cavity by a transesophageal hiatal operation under laparotomy. Followed by gastric tube reconstruction by the posterior sternal route. The postoperative course was uneventful. In this case, taking advantage of the thoracoscopic approach from both sides, the tumor could be safely resected without unreasonable traction. Furthermore, the prone position has the advantage that bilateral thoracoscopic operation is possible without changing the position. This technique could also be applied for the excision of esophageal cancer involving the left side.